CONCEPTUAL MODEL DEVELOPMENT OF REGIONAL INNOVATION DRIVING FACTORS IN CIANJUR REGENCY - Anita Ilmaniati; Isma Masrofah (Universitas Ahmad Dahlan Indonesia, 2021)
Strengthening regional competitiveness as a derivative of strengthening national competitiveness encourages every region in Indonesia to design a regional innovation system (SIDa), including Cianjur Regency. One of the activity programs at SIDa that have been carried out in 2019 is an innovation competition. Based on the evaluation of the innovation competition activities, it is known that the level of community participation is still very low. This indicates that the level of innovation enthusiasm is still low in the Cianjur community. This study aims to formulate a conceptual model between the factors of attitude towards innovation and knowledge awareness of the innovation enthusiasm of the people of Cianjur Regency. The research was carried out by conducting a literature review based on related previous studies. In this study, operationalization variables and item indicators were also carried out, as well as testing the reliability and validity of the measurement scale using initial data. The results of this study are in the form of a conceptual model that links attitudes towards innovation and awareness of knowledge towards innovation enthusiasm along with the level of reliability and validity of the measurements.